2023
DOI: 10.3748/wjg.v29.i39.5452
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F synthase promotes oxaliplatin resistance in colorectal cancer through prostaglandin F-dependent and F-independent mechanism

Yi-Jun Wang,
Xiao-Li Xie,
Hong-Qun Liu
et al.

Abstract: Small extracellular vesicles (exosomes) are important components of the tumor microenvironment. They are small membrane-bound vesicles derived from almost all cell types and play an important role in intercellular communication. Exosomes transmit biological molecules obtained from parent cells, such as proteins, lipids, and nucleic acids, and are involved in cancer development. MicroRNAs (miRNAs), the most abundant contents in exosomes, are selectively packaged into exosomes to carry out their biological funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, the lingering question is how the initial treatment might in uence subsequent prognosis for patients who experience recurrence. It was pertinent to examine whether the initial standard treatment including chemotherapy or radiotherapy, could induce heightened drug resistance [17][18][19][20][21] and result in a more invasive tumor pro le [22]. Our ndings revealed that patients with high-risk tumors who initially received primary surgery were administered less chemotherapy before recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lingering question is how the initial treatment might in uence subsequent prognosis for patients who experience recurrence. It was pertinent to examine whether the initial standard treatment including chemotherapy or radiotherapy, could induce heightened drug resistance [17][18][19][20][21] and result in a more invasive tumor pro le [22]. Our ndings revealed that patients with high-risk tumors who initially received primary surgery were administered less chemotherapy before recurrence.…”
Section: Discussionmentioning
confidence: 99%